PHC LEADERSHIP CHARACTERISTICS, COMMUNITY HEALTH WORKER PERFORMANCE, AND MATERNAL BEHAVIOR IN STUNTING REDUCTION: SYSTEMATIC REVIEW - Yuniastini, Yuniastini; Barusman, Yusuf Sulfarano; Barusman, Andala Rama Putra; Habiburrahman, Habiburrahman; Amatiria, Gustop; Putri, Gita Leviana; Marthalena, Yenny; Sunarmi, Sunarmi (LPPM Universitas Jambi, 2026)
Stunting remains a critical global health challenge, yet the role of Primary Health Care (PHC) facility leadership in driving nutritional outcomes through community health worker (CHW) pathways remains poorly synthesized. This systematic review aims to examine leadership models employed by PHC facility heads and their association with stunting reduction, mediated by CHW performance and maternal health behavior change. A systematic search of PubMed, Scopus, and Elsevier databases was conducted following PRISMA guidelines. Original research articles examining PHC leadership, CHW supervision, and nutritional outcomes in children under five were included. Studies lacking leadership variables or stunting-related outcomes were excluded. Quality assessment utilized standardized appraisal tools. Twelve studies met inclusion criteria. Supportive supervision (9/12), training investment (10/12), stakeholder coordination (8/12), and resource mobilization (7/12) were key leadership characteristics associated with improved outcomes. Transformational leadership enhanced CHW motivation, task completion, and retention. A mediating pathway was identified: effective leadership improved CHW performance, which enhanced maternal antenatal care utilization, dietary diversity, and breastfeeding practices, contributing to stunting reduction. PHC leadership serves a catalytic function in stunting reduction through CHW capacity strengthening and community engagement. This review uniquely delineates the leadership–CHW–maternal behavior–stunting causal pathway, addressing a critical gap in implementation science. Future studies should employ longitudinal designs measuring leadership interventions' direct impact on anthropometric outcomes, and develop validated instruments for assessing PHC leadership competencies in low-resource settings.